Mental–Perceptual Abilities and Giftedness Identification in Children Gifted for Music: A Study Across Musical and Non-Musical Families - López-Íñiguez, Guadalupe; Angel-Alvarado, Rolando (MDPI, 2026)
Children gifted for music are often described as possessing heightened perceptual and sensory abilities, yet little is known about how these abilities are understood within different family contexts or how giftedness is experienced as an identity. This mixed-methods study examined alignment between gifted children’s and parents’ perceptions of children’s mental–perceptual abilities, the role of parental musical background, and how giftedness is explained and emotionally negotiated. Twenty-two children identified as gifted for music and 25 parents completed a survey based on Gagné’s Differentiated Model of Giftedness and Talent assessing six mental–perceptual abilities, followed by semi-structured interviews. Quantitative analyses revealed a strong positive association between child and parent ratings, alongside a consistent tendency for parents to provide higher evaluations. Parental professional musical background did not significantly moderate alignment but was associated with greater variability in both children’s and parents’ ratings. Qualitative findings indicated shared experiential understandings of ability across families, alongside systematic differences in evaluative frameworks: musician parents more frequently drew on technical, comparative, and training-based standards, whereas non-musician parents relied on affective and everyday observations. Children across contexts often expressed modesty or ambivalence toward being labeled gifted, while parents balanced pride with concern about pressure. Overall, perceptions of mental–perceptual ability emerged as relationally constructed within family environments that shape how musical giftedness is recognized and supported.
Keywords: musiikki; lahjakkuus; musiikkikasvatus; lapset (ikäryhmät); erityiskasvatus; musiikkipsykologia; musikaalisuus